Perbedaan Kebugaran Jasmani Berdasarkan Status Sosial Pada Peserta Didik Sekolah Dasar Kelas 3 - Tiara Tiara; Haura Athaya; Y. Touvan Juni Samodra (Journal of Sport Coaching and Physical Education, 2024)
The socio-economic conditions of students' parents vary, these differences affect educational facilities, food intake, child development, and students' physical fitness. Good physical fitness can improve learning achievement. This research aims to compare physical fitness based on students' social status, with the hope of increasing the physical fitness of all social statuses. Quantitative descriptive research, with a sample of class III students at SDN 16 Rasau Jaya and SD Mujahidin, a sample of 40 people consisting of 20 people from each school, using purposive sampling techniques. With research characteristics, namely class III students, and aged 6-9 years. Data collection uses the Indonesian Physical Fitness Technique (TKJI) measurement test technique. The research results show that SD Mujahidin has physical fitness in the good category of 10%, moderate 60%, poor 30%, while SDN 16 Rasau Jaya has the moderate category of 70%, and poor 30%. SD Mujahidin has better physical fitness than SDN 16 Rasau Jaya, so there is a difference in the physical fitness of SD Mujahidin and SDN 16 Rasau Jaya. The difference can be seen from 10% of Mujahidin Elementary School being in the good category, with adequate facilities, sports teachers, and middle to upper socio-economic status. On the other hand, SDN 16 Rasau Jaya does not have students in the good category, due to inadequate facilities, no sports teacher, and middle socio-economic status